Integrated Of Islamic Education in Ideology Liberalism - Sapri Sapri (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
Educational liberalization is a contemporary educational movement in which education must take cultural action for cultural freedom and revolution. The concept of liberalism about education implicitly leads to the idea of integrative education. It is the same with Islamic education, where educational liberalism emphasizes the principle of problem-solving when referring to the concept of the main thing about academic liberalism. The expected goal is about integration between theory and practice. This paper uses qualitative concept research. Data sources come from related articles and books. Then analyzed and described descriptively. The study results indicate that the concept of educational liberalism is under integrative education (idea) or in line with the idea of Islamic education. While the idea of Integrative Islamic education in the ideology of liberalism can be seen in 4 ways. 1) foundation, 2) objectives, 3) methods, and 4) evaluation.